2020
DOI: 10.1080/09540105.2020.1743647
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of structural characteristics and immunoregulatory activities of polysaccharides from four natural plants

Abstract: Polysaccharides have various bioactivities including anti-tumour, antioxidant and immunoregulation, which are correlated with their structural characteristics. Here, four polysaccharides from Glycyrrhiza uralensis (GUPS), Pleurotus ferulae (PFPS), Triticum aestivum (TAPS) and Oryza sativa (OSPS) were purified to compare their structural characteristics and immunoregulatory activities. The data showed that TAPS, OSPS, GUPS and PFPS contained different monosaccharide components and had distinctly structural char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…It is used to cure pimples, female disorders, respiratory ailments (cough, asthma, coryza and bronchitis), dysentery and tumors (Kausa et al, 2016). E. hirta contains phytochemicals such as: triterpenoids, sterols, alkaloids, glycosides, flavonoids, tannins, phenols, choline and shikimic acid while some of the reported activities include its use as an antispasmodic, antiasthmatic, expectorant, anticatarrhal, antisyphilitic, antibacterial, antidiabetic, antivenom, wound healing, antimalarial, immunostimulatory, antithrombocytopenic, antioxidant, anticancer, antiallergy, anti-inflammatory and diuretic (Gopi et al, 2016;Kanedi, 2017;Anjum et al, 2017;Kikete et al, 2018;Thabet et al, 2018;Aleksandrov et al, 2019;Rahman et al, 2019;Uzor, 2020;Mahabati et al, 2020;Tran et al, 2020;Gokulprasath et al, 2021). However, El-Mahmood (2009) reported that E. hirta is a very popular herb amongst practitioners of traditional medicine and some of its local names in Nigeria include "nonon furchiya" in Hausa, "tepel" in fulzfulde, "Harvom" in Kaka and "Hammock sand mat" (Florida) while the exudate of the stem is used to treat eye and ear infections in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…It is used to cure pimples, female disorders, respiratory ailments (cough, asthma, coryza and bronchitis), dysentery and tumors (Kausa et al, 2016). E. hirta contains phytochemicals such as: triterpenoids, sterols, alkaloids, glycosides, flavonoids, tannins, phenols, choline and shikimic acid while some of the reported activities include its use as an antispasmodic, antiasthmatic, expectorant, anticatarrhal, antisyphilitic, antibacterial, antidiabetic, antivenom, wound healing, antimalarial, immunostimulatory, antithrombocytopenic, antioxidant, anticancer, antiallergy, anti-inflammatory and diuretic (Gopi et al, 2016;Kanedi, 2017;Anjum et al, 2017;Kikete et al, 2018;Thabet et al, 2018;Aleksandrov et al, 2019;Rahman et al, 2019;Uzor, 2020;Mahabati et al, 2020;Tran et al, 2020;Gokulprasath et al, 2021). However, El-Mahmood (2009) reported that E. hirta is a very popular herb amongst practitioners of traditional medicine and some of its local names in Nigeria include "nonon furchiya" in Hausa, "tepel" in fulzfulde, "Harvom" in Kaka and "Hammock sand mat" (Florida) while the exudate of the stem is used to treat eye and ear infections in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…P. eryngii var. ferulae is edible and has several medicinal properties, including anti-tumor, antioxidant, anti-obesity, and immunoregulatory properties [4][5][6][7]. Moreover, P. eryngii var.…”
Section: Introductionmentioning
confidence: 99%